Characteristics of Oral Hemangioma and Vascular Malformation Cases: A Study at Hasan Sadikin General Hospital, 2019-2023 - Yashinta Rachmavita; Harmas Yazid Yusuf; Melita Sylvyana (Syntax Corporation Indonesia, 2024)
This observational retrospective study conducted at Hasan Sadikin General Hospital (RSHS) in Bandung from January 2019 to February 2023 aimed to characterise oral hemangiomas and vascular malformations. Out of 52 medical records analysed, infantile hemangioma was the most common type (17%), typically presenting between ages 13 to 24 years. Predominantly located around the lip, tongue, and buccal mucosa, it seldom caused bleeding or pain, with women being more affected. Treatment often involved sclerotic agent injections. Venous malformations accounted for 58% of vascular malformations, showing similar age of presentation and distribution as hemangiomas, and were also treated with sclerotic agents. Accurate diagnosis and tailored treatment are crucial due to the diverse nature of these anomalies. Early detection using imaging techniques like ultrasound and CT angiography is imperative, given the potential impact on patients, including pain, swelling, and cosmetic concerns, particularly in the head and neck area. However, treatment approaches vary based on factors such as type and size, necessitating further research to refine diagnostic and therapeutic strategies and optimise patient outcomes.